EMPOWERING COFFEE FARMERS IN SUKASARI, MOUNT MANGLAYANG, THROUGH NATIONAL STANDARDS OF INDONESIA (SNI) FOR POST-HARVEST QUALITY IMPROVEMENT TO ACCESS INTERNATIONAL MARKETS - Wahdiniwaty, Rahma; Syafei, M. Yani; Haryadi, Yudi; Nurdiansyah, Deni (GoAcademica CRP, 2025)
Coffee is one of Indonesia’s most significant agricultural commodities, yet post-harvest handling among smallholder farmers remains suboptimal. This community service program aimed to empower coffee farmers in Sukasari, Mount Manglayang, West Java, by introducing post-harvest storage practices that comply with the Indonesian National Standards (SNI). The program was conducted in July 2025 through a combination of training, demonstration, and participatory approaches with farmer groups. Pre-surveys revealed that more than 70% of farmers stored coffee beans using traditional methods, resulting in quality degradation and low market value. The intervention included training sessions, technical demonstrations on the use of simple storage racks, and the introduction of tools such as moisture meters and thermohygrometers. Evaluation results indicated a significant improvement in farmers’ knowledge, with post-test scores showing more than 40% increase compared to pre-tests. Farmers were also actively involved in drafting a Standard Operating Procedure (SOP) for coffee storage, which is now used as a reference by their cooperatives. The findings highlight the importance of participatory capacity building in enhancing product quality, ensuring better market access, and aligning with Sustainable Development Goals (SDGs), particularly goals 1 (No Poverty), 8 (Decent Work and Economic Growth), and 12 (Responsible Consumption and Production).